Jointly Rayleigh lifetime products in the presence of competing risks model - Badr Souha K.; Abu-Zinadah Hanaa (Open Physics, 2022)
In this article, we are applying the competing risks model of product from two different lines of production. So, the comparative life test is done under type-II censoring scheme with consideration of only two independent causes of failure. The statistical analysis procedures are developed considering joint sample of production and its life distributed with the Rayleigh lifetime distribution. The point estimation and the corresponding asymptotic confidence interval of the model parameters under maximum likelihood are constructed. Two bootstrap confidence intervals, bootstrap-pp, and bootstrap-tt, are discussed. Also, Bayesian approach to estimate point and credible interval is constructed. The estimation results are discussed through data set analyses. The validity of theoretical results is assessed and compared through Monte Carlo study. Finally, some of the points are reported as a brief comment.